2017
DOI: 10.1504/ijemr.2017.10008550
|View full text |Cite
|
Sign up to set email alerts
|

Influence of user generated content in online shopping: impact of gender on purchase behaviour, trust, and intention to purchase

Abstract: To investigate differences in gender in the influence of user generated content (UGC) on purchase behaviour, trust, and intention to purchase. UGC refers to online comments/opinions which can influence other users' purchase decisions. Quantitative data gathered through a survey of 232 undergraduates at an American university. UGCs have a greater influence on purchase intentions and trust for females. No gender differences were found in terms of UGC's influence for a gender-neutral product, propensity to read U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
(86 reference statements)
2
9
0
Order By: Relevance
“…From the photo posting perspective, the current research suggests that visual content is significantly more stimulating than text alone (Vazquez et al 2021). Additionally, reviews are found to contribute to the hedonic online shopping experience because consumers find pleasure in this rather than only looking at the reviews for informative purposes which would contribute to a utilitarian need (Sethna et al, 2017).…”
Section: Shein?mentioning
confidence: 76%
See 3 more Smart Citations
“…From the photo posting perspective, the current research suggests that visual content is significantly more stimulating than text alone (Vazquez et al 2021). Additionally, reviews are found to contribute to the hedonic online shopping experience because consumers find pleasure in this rather than only looking at the reviews for informative purposes which would contribute to a utilitarian need (Sethna et al, 2017).…”
Section: Shein?mentioning
confidence: 76%
“…The publishing of information online is shifting from the previous publisher-centric model, driven by organizations, towards a user-centric environment (Sethna et al, 2017). Daugherty et al (2008) express user-generated content (UGC) as content published by users on an online platform.…”
Section: User-generated Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is consistent with several previous studies that found trust to be a critical factor affecting the intention to behave. For instance, consumers were observed to make a purchasing decision when they trust a product (Bonsón Ponte et al, 2015;Chinomona et al, 2013;Raharja et al, 2017;Sethna et al, 2017;Weisberg et al, 2011). Therefore, as an official partner in the forthcoming mass COVID-19 vaccination program, the government must pay more attention to establishing public trust to ensure the successful completion of the program.…”
Section: Discussionmentioning
confidence: 99%